Design and preparation of MoO2/MoS2 as negative electrode materials for supercapacitors. (15th December 2016) - Zhang, Tong; Kong, Ling-Bin; Liu, Mao-Cheng; Dai, Yan-Hua; Yan, Kun; Hu, Bing; Luo, Yong-Chun; Kang, Long
Abstract: In this work, the MoO2 /MoS2 composite material with unique flower-like microsphere structure is prepared via a facile hydrothermal synthesis. Furthermore, the composite material is served as negative electrode for supercapacitors. Ascribe to the synergistic effect, including the improved electron conductivity, the coexistence of two energy storage mechanisms, and a stable flower-like microsphere structure, the as-fabricated MoO2 /MoS2 exhibits a high specific capacitance of 433.3 F g − 1 at a scan rate of 5 mV s − 1 and a superior cycling stability of 84.41% retention after 5000 cycles compared to that of pure MoO2 (33.33% retention after 2000 cycles) and pure MoS2 (58.33% retention after 2000 cycles) at a current density of 1 A g − 1 in 1 M Na2 SO4 electrolyte. Moreover, we also synthesize a series of MoO2 /MoS2 electrode materials, which are used to further illustrate the synergistic effect in MoO2 /MoS2 composite materials. This work signifies such materials as negative electrodes exhibit bright application prospects for supercapacitors. Graphical abstract: The MoO2 /MoS2 flower-like microspheres was successfully designed and prepared. Moreover, it was also served as negative electrode with excellent electrochemical performance for supercapacitors. Highlights: MoO2 /MoS2 is successfully synthesized and is firstly served as negative electrodes for supercapacitors. The MoO2 /MoS2 electrode displays a high specific capacitance of 433.3 F g -1 at a scan rate of 5 mV s -1 . The MoO2 /MoS2 electrode indicates higher specific capacitance than that of pure MoO2 and pure MoS2 . The capacitance retention of MoO2 /MoS2 is 84.41% after 5000 cycles, which is superior to pure MoO2 and pure MoS2 .